2018
DOI: 10.1074/jbc.ra118.002580
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypo-O-GlcNAcylation on Drosophila development

Abstract: Post-translational modification of serine/threonine residues in nucleocytoplasmic proteins with GlcNAc (O-GlcNAcylation) is an essential regulatory mechanism in many cellular processes. In Drosophila, null mutants of the Polycomb gene O-GlcNAc transferase (OGT; also known as super sex combs (sxc)) display homeotic phenotypes. To dissect the requirement for O-GlcNAc signaling in Drosophila development, we used CRISPR/Cas9 gene editing to generate rationally designed sxc catalytically hypomorphic or null point m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 75 publications
(105 reference statements)
1
33
0
Order By: Relevance
“…Lack of functional OGT causes lethality and developmental arrest in most metazoan model organisms, including mice, frogs, zebrafish, and fruit flies (19, 22, 24, 61). To probe if the N567K mutation directly affects OGT catalytic activity in vivo, we exploited the genetically tractable system D. melanogaster , where phenotypes arisen due to null and hypomorphic alleles of sxc (the fly ogt ortholog) have been described (62, 63). Drosophila sxc null mutants ( sxc 1 and sxc 6 ) die at the pharate adult stage with homeotic transformation defects (62).…”
Section: Resultsmentioning
confidence: 99%
“…Lack of functional OGT causes lethality and developmental arrest in most metazoan model organisms, including mice, frogs, zebrafish, and fruit flies (19, 22, 24, 61). To probe if the N567K mutation directly affects OGT catalytic activity in vivo, we exploited the genetically tractable system D. melanogaster , where phenotypes arisen due to null and hypomorphic alleles of sxc (the fly ogt ortholog) have been described (62, 63). Drosophila sxc null mutants ( sxc 1 and sxc 6 ) die at the pharate adult stage with homeotic transformation defects (62).…”
Section: Resultsmentioning
confidence: 99%
“…For such attempts, either transgenes expressing the human mutant proteins, or transgenes expressing the Drosophila genes with engineered, analogous mutations, can be used. Alternatively, gene replacement by homologous recombination and CRISPR/Cas9 genome-editing approaches now allow manipulation of the fly gene at its endogenous locus (de Brouwer et al, 2018; Mariappa et al, 2018) (Fig. 2B).…”
Section: Future Outlookmentioning
confidence: 99%
“…In this regard, sxc 1 and sxc 6 mutant cuticles display no denticle belts ( Figure 1E) while sxc 3 , sxc 5 , and sxc 7 cuticles display hypotrophied denticle belts ( Figure 1F). We also showed that the cuticle phenotype of animals harboring the sxc 1 allele in trans to a non-complementing deficiency is indistinguishable from that of sxc 1 homozygotes ( Figure 1G), providing genetic evidence that the sxc 1 nonsense allele is, as previously suspected, null (Mariappa et al, 2018;Sinclair et al, 2009). Given that sxc 1 exhibits the greatest level of embryonic lethality, the strongest cuticle defect, and is genetically defined as null, we chose this allele for all further experiments.…”
Section: Resultsmentioning
confidence: 82%